2022
DOI: 10.1097/meg.0000000000002363
|View full text |Cite
|
Sign up to set email alerts
|

Colonic mucosal eosinophilia and immunohistochemical expression of COX-2 and NF-kB in patients with irritable bowel syndrome

Abstract: Background There is growing evidence that eosinophilic infiltration can release mediators which are harmful to the intestinal epithelium in patients with irritable bowel syndrome (IBS). Although cyclooxygenase 2 (COX-2) and nuclear factorkappa beta (NF-kB) expression had been previously reported to increase in many inflammatory conditions, there is a paucity in data investigating their expressions in IBS. Our aim was to evaluate colonic mucosal eosinophilia and immunohistochemical expression of COX-2 and NF-kB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The gene expression profile of different markers, including Vegf-α, Cox-2 and Trpv-1 , was significantly increased in the IBS group in comparison with Non-IBS control ( Figure 4 a–c, respectively). Previous studies have described higher levels of these mediators in IBS patients [ 44 , 45 , 46 , 47 ]. Remarkably, the probiotic and rifaximin treatments significantly reduced their expression ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression profile of different markers, including Vegf-α, Cox-2 and Trpv-1 , was significantly increased in the IBS group in comparison with Non-IBS control ( Figure 4 a–c, respectively). Previous studies have described higher levels of these mediators in IBS patients [ 44 , 45 , 46 , 47 ]. Remarkably, the probiotic and rifaximin treatments significantly reduced their expression ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“… 82 , 105 , 106 Clinical tests have shown that the number of intestinal mucosa EG in IBS patients rises, and intracellular CRH expression increases, which is positively correlated with intestinal symptoms and depression. 107 - 109 …”
Section: Crh In Peripherymentioning
confidence: 99%
“…Excessive lipopolysaccharides (LPS) can activate inflammation-related cellular signaling pathways, including nuclear factor-kappa B (NF-κB), activator protein-1 (AP-1), and mitogen-activated protein kinases (MAPKs) [ 4 ]. NF-κB family members regulate the functioning of several proinflammatory cytokines, transcription factors, cell surface receptors, and adhesion molecules, which play major roles in intestinal inflammation [ 5 ]. Activated inflammatory cells produce additional cytokines such as tumor necrosis factor-α (TNF-α), interleukin-(IL)-1β, and IL-6 along with nitric oxide (NO), prostaglandin E2 (PGE 2 ) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%